2015
DOI: 10.1111/gwmr.12122
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Phytoscreening and Direct‐Push‐Based Site Investigation at a Rural Megasite Contaminated with Chlorinated Ethenes

Abstract: The reliable characterization of subsurface contamination of spatially extended contaminated sites is a challenging task, especially with an unknown history of land use. Conventional technologies often fail due to temporal and financial constraints and thus hinder the redevelopment of abandoned areas in particular. Here we compare two site screening techniques that can be applied quickly at relatively low cost, namely Direct Push (DP)‐based groundwater sampling and tree core sampling. The effectiveness of both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Tree-core, groundwater, and soil samples were collected at the Vienna Wells site from May 2013 to April 2016. Global positioning system (GPS) locations were collected for each tree using either a Trimble GeoExplorer XH (Trimble Navigation Limited, Sunnyvale, California) with a submeter accuracy or using smart phones (iPhone 5 [Apple, Cupertino, California] and Samsung S5 [Samsung, Seoul, South Korea]), which have been shown to have an average accuracy of about 5–8 m. , All tree-core, averaged groundwater (2013–2016 sample concentrations), and soil data used in this paper are available at U.S. Geological Survey (USGS) ScienceBase, . Raw (nonaveraged) groundwater data are available in the USGS National Water Information System (NWIS), (see SI Table S1 for NWIS station IDs).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tree-core, groundwater, and soil samples were collected at the Vienna Wells site from May 2013 to April 2016. Global positioning system (GPS) locations were collected for each tree using either a Trimble GeoExplorer XH (Trimble Navigation Limited, Sunnyvale, California) with a submeter accuracy or using smart phones (iPhone 5 [Apple, Cupertino, California] and Samsung S5 [Samsung, Seoul, South Korea]), which have been shown to have an average accuracy of about 5–8 m. , All tree-core, averaged groundwater (2013–2016 sample concentrations), and soil data used in this paper are available at U.S. Geological Survey (USGS) ScienceBase, . Raw (nonaveraged) groundwater data are available in the USGS National Water Information System (NWIS), (see SI Table S1 for NWIS station IDs).…”
Section: Methodsmentioning
confidence: 99%
“…18−21 Tree-coring as a screening tool for site characterization has gained national and international regulatory acceptance by the United States (U.S.) Environmental Protection Agency (EPA) in 2008 22 and the European Union in 2012. 23 Although recent research has addressed the use of trees to measure contaminant concentrations in water 24 and soil gas in the natural environment, 11 the authors are aware of only limited studies 22,25 that have compared the use of tree-core sample collection and analysis of VOCs to traditional methods of VOC sampling to assess VI risks to the built environment. Additionally, the impact of tree characteristics (such as tree species, size, and rooting characteristics) on relationships between groundwater, soil, and vapor concentrations and in planta concentrations is fairly well-known, 22,26,27 but little is known about how these tree characteristics affect the spatial representation of plant sampling.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, numerous studies have shown the linkage between contaminated soil and uptake of volatile organic compounds (VOCs) by vegetation. 118,21,23 As a result, vegetation (e.g., trees) have been used for both remediation 12,5,7,22 and phytoscreening 4,6,1013, 15, 17–19, 2425, 27, 3334 applications. Phytoscreening continues to receive attention as a lower-cost, broad-scale screening tool for assessing the occurrence and distribution of VOCs in subsurface environments.…”
Section: Introductionmentioning
confidence: 99%
“…Phytoscreening is based on the sampling and analysis of plant tissues (i.e., tree core, branch, leaf) as a surrogate for sampling of soil, soil gas, and groundwater. Several field studies have demonstrated its usefulness as a characterization method, particularly for volatile organic constituents (VOCs) (e.g., Vroblesky et al, 1999, 2004; Struckhoff et al, 2005; Gopalakrishnan et al, 2007, 2011; Larsen et al, 2008; Sorek et al, 2008; Burken et al, 2011; Limmer et al, 2011, 2013, 2014; Wahyudi et al, 2012; Wittlingerova et al, 2013; Algreen et al, 2015; Rein et al, 2015; Yung et al, 2017).…”
Section: Introductionmentioning
confidence: 99%